2019
DOI: 10.3389/fpsyg.2019.02786
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions at Work and Job Crafting: Results From Two Prospective Studies

Abstract: To date, research confirmed the effects of job crafting on the functioning of employees and organizations. In contrast, the evidence for the predictors of job crafting is limited. Based on broaden-and-build (B&B) theory, it may be assumed that high positive emotions at work would predict high job crafting behaviors at follow-ups. In line with social cognitive theory (SCT), it may be hypothesized that self-efficacy would mediate the relationship between positive emotions at work and following job crafting behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 72 publications
(141 reference statements)
2
14
0
3
Order By: Relevance
“…Thus, when facing demanding job situations, it is likely that individuals with higher levels of hedonic and eudaimonic feelings will more often evaluate those demands positively and possibly overcome (i.e., good rather than bad) as well as see them as opportunities for utilizing and developing abilities to experience personal growth. This is also in line with [47], in which the authors reported that positive emotions at work did not decrease hindering demands but increased challenging demands.…”
Section: Positive Trait Emotionssupporting
confidence: 88%
“…Thus, when facing demanding job situations, it is likely that individuals with higher levels of hedonic and eudaimonic feelings will more often evaluate those demands positively and possibly overcome (i.e., good rather than bad) as well as see them as opportunities for utilizing and developing abilities to experience personal growth. This is also in line with [47], in which the authors reported that positive emotions at work did not decrease hindering demands but increased challenging demands.…”
Section: Positive Trait Emotionssupporting
confidence: 88%
“…We can see that patients and Table 3 The correlation of job well-being, emotional intelligence, empathy, and communication satisfaction (r value, n = 1475) colleagues are an important source of nurses' job wellbeing. As a positive emotion, job well-being can improve personal and organisational performance and enable nurses to show higher work enthusiasm and creativity [33]. Therefore, it is necessary for nursing managers and educators to implement relevant interventions to improve nurses' job well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This departs from previous studies on job crafting that have adopted the broaden-and-build theory primarily to elucidate the organization-related antecedents of job crafting, eg, Rogala, Cieslak. 65 Similarly, our research is among the first to identify an individual-related antecedent’s (Confucianism) positive effect on job crafting. Indeed, as a key cultural value rooted in traditional Chinese society, Confucianism still has a lingering influence on employees’ attitudinal and behavioral outcomes in contemporary workplaces.…”
Section: Discussionmentioning
confidence: 74%